Influence of Gap Blade Geometry on the Energy Performance of Low-Specific-Speed Centrifugal Pumps - Aneta Nycz; Janusz Skrzypacz; Przemysław Szulc (Energies)
This study investigates the influence of modifications in the geometry of the blades—specifically, the introduction of a gap blade into the impeller blades—on the hydraulic performance of a low specific speed centrifugal pump. The research addresses the problem of efficiency losses in such pumps and explores whether implementing a blade gap can improve energy characteristics without altering the primary flow path. A set of impellers with different gap configurations was designed and manufactured using 3D printing. Experimental tests were carried out on a laboratory test rig equipped with standard pressure, flow, and power measurement instruments. Next, numerical simulations were performed using CFD methods in Ansys CFX, using the k-ω SST turbulence model. The results show that impellers with gap blades achieved higher efficiency—up to 4 percentage points compared to the reference design—and an increase in the maximum pump capacity. CFD analysis confirmed more uniform velocity distributions and reduced separation zones in the interscapular channels, along with a smoother pressure gradient across the blade surfaces. The results demonstrate that modifying impeller geometry using gap blades can improve hydraulic efficiency and expand the range of stable operation. These conclusions support further research on performance optimisation in low-specific-speed centrifugal pumps.